Portfolio Theory and Management 2013
DOI: 10.1093/acprof:oso/9780199829699.003.0005
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Risk Tolerance

Abstract: Assessing risk tolerance is an important part of advising clients about portfolio selections. The expected utility approach underlying portfolio advice based on financial economics assumes that a household has some level of risk aversion that determines its utility from different wealth or consumption levels. Therefore, a household's risk aversion or its inverse—risk tolerance—is a key factor in determining the optimal portfolio for a household. Risk tolerance measures that offer choices without context as to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…An examination of the descriptive (Barber and Odean, 2001;Yao et al, 2011;Ansari et al, 2023). As stated by earlier studies, the younger generation is more likely to take financial risks than the older generation (Hanna et al, 1998;Al-Tamimi and Kalli, 2009;Yao et al, 2011). The present study also found evidence that respondents aged 28 to 37 were more inclined to take risks than other groups.…”
Section: Discussionsupporting
confidence: 82%
“…An examination of the descriptive (Barber and Odean, 2001;Yao et al, 2011;Ansari et al, 2023). As stated by earlier studies, the younger generation is more likely to take financial risks than the older generation (Hanna et al, 1998;Al-Tamimi and Kalli, 2009;Yao et al, 2011). The present study also found evidence that respondents aged 28 to 37 were more inclined to take risks than other groups.…”
Section: Discussionsupporting
confidence: 82%
“…Besides, it is an elusive concept that appears to be influenced by a number of predisposing factors (Trone, Allbright, & Taylor, 1996) such as demographic, environmental, and psychosocial factors. The extant literature shows that among all the factors, demographic characteristics are the most widely investigated determinants of FRT (e.g., Grable & Lytton, 1999; Grable, 1997; Moreschi, 2011; Wang & Hanna, 1998). In addition, demographic characteristics could be used to differentiate retail investors in terms of FRT and classify them into different FRT categories (Grable & Lytton, 1999).…”
mentioning
confidence: 99%
“…Despite the importance of FRT in financial and investment decision-making, specific theory related to the assessment and prediction of FRT is very limited (Hanna, Gutter, & Fan, 1998), but theories related to non-financial decisions (i.e., use of drug and alcohol) widely exist. For example, risk attitudes and behaviours of an adolescent on the basis of predisposing factors were investigated by Irwin Jr (1993).…”
mentioning
confidence: 99%
“…For Hunter, risk tolerance may vary depending on the type of decision in which an individual is involved. Corroborating this idea, Hanna et al (2013) pointed out that when a decision involves a small monetary amount, even if some people are generally risk averse, they may appear neutral or even willing to accept the risk.…”
Section: Research Model and Propositionsmentioning
confidence: 99%